GC-MS analysis of bioactive compounds and comparative antibacterial potentials of aqueous, ethanolic and hydroethanolic extracts of Senna alata L against enteric pathogens - Mohanasundaram S; Doss VA; Haripriya G; Varsha M; Daniya S; Madhankumar (International Journal of Research in Pharmaceutical Sciences, 2023)
In this investigation, aqueous, ethanolic and hydroethanolic extracts of Senna alata was analysed for antibacterial property. For this, extracts of Senna alata was studied against selected enteric pathogenic bacteria includes Bacillus subtilis ATCC441, Staphylococcus aureus ATCC25923, E.coli ATCC25922, Pseudomonas aeruginosa ATCC2785, Enterococcus feacalis ATCC29212 and Klebsiella pneumoniae ATCC15380 and showed growth inhibition activity. The results of different extracts were compared based on zone of inhibition in mm and it was found that, hydroethanolic extract was found to be most effective. This hydroethanolic was further subjected into GC-MS analysis to identify the bioactive compounds present in the plant extract. We have found 7 different compounds are present in the extract.